COMMUNICATION EFFECTIVENESS POST PANDEMI COVID 19 - Ahmad Fauzi Batubara (Proceeding International Seminar of Islamic Studies, 2023)
The impact of the Covid 19 pandemic forced changes in the way we communicate. Communication that was previously carried out directly face to face shifted to communication using information technology. Changes in communication are applied to almost all aspects of life such as education, government, trade, and so on. On the other hand, the development of information and communication technology in the global world is happening very fast. The flow of information in particular runs very quickly. Limited interaction that occurred during the Covid 19 pandemic. For some people who are familiar with various information technologies, this is an opportunity where various activities can be carried out more efficiently. However, for ordinary people, most of whom do not really understand information technology, this is a new problem. Where people who do not understand the technology must catch up. Not to mention the provision of facilities that must exist in carrying out virtual communication, of course it can even become a burden. Using the Media System Dependency Model approach, the author conducted a study of the communication phenomenon after the Covid 19 pandemic in Indonesia. The conclusion from this paper is that the government in particular must be able to arrange surveillance and control activities for public safety in communicating using information technology.